2021
DOI: 10.1111/are.15371
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo evaluation of antimicrobial activity of Zooshikella marina against pathogenic bacteria causing vibriosis in aquaculture

Abstract: Vibriosis is a potentially serious infectious disease caused by Vibrio spp. These bacteria are Gram negative and are ubiquitous in marine environment and in estuarine ecosystems (Austin, & Austin, 2007). They can be found free-living in the water column, as part of a biofilm, or in association with a host (Thompson et al., 2004).Vibriosis affects large numbers of fish and shellfish species, both cultured and feral. A number of species under the genus Vibrio, for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The pathogenicity of V. parahaemolyticus is closely related to a variety of virulence factors, including the iron absorption system, lipopolysaccharides, proteases, outer membrane proteins, the adhesion factor type III secretion system, and the type VI secretion system ( He et al, 2020 ; Puangpee and Suanyuk, 2021 ). Biofilms are an important survival and pathogenic mechanism of V. parahaemolyticus , which are difficult to remove ( Hall-Stoodley et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of V. parahaemolyticus is closely related to a variety of virulence factors, including the iron absorption system, lipopolysaccharides, proteases, outer membrane proteins, the adhesion factor type III secretion system, and the type VI secretion system ( He et al, 2020 ; Puangpee and Suanyuk, 2021 ). Biofilms are an important survival and pathogenic mechanism of V. parahaemolyticus , which are difficult to remove ( Hall-Stoodley et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Piscidin-4 can bind to the lipopolysaccharide on the outside of the bacterial membrane via an electrostatic gravitational force, disturbing the cell wall in that area and altering its stability, which allows it to cross the area smoothly, come to the proximity of the cell membrane, and eradicate the microbial biofilm. Piscidin-4 was highly active against Gram-negative bacteria, including Vibrio spp., that pose a serious threat to aquaculture and possessed immunomodulatory properties [ 9 , 10 ]. Different studies have shown that both AMPs, NZ2114 and Piscidin-4, have weak host toxicity and low hemolytic activity against vertebrates, suggesting that they are more suitable for antibacterial studies [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%